Do Implicit Barriers Matter for Globalization? - Carrieri, Francesca; Chaieb, Ines; Errunza, Vihang (Review of Financial Studies, 2013)
Market liberalization may not result in full market integration if implicit barriers are important. We test this proposition for investable and non-investable segments of twenty-two emerging markets (EMs). We also measure the degree of integration for six major developed markets (DMs) as a meaningful benchmark. We find that while the DMs are close to fully integrated, both EM segments are not effectively integrated with the global economy. We quantify the importance of implicit barriers and show that better institutions, stronger corporate governance, and more transparent markets in EMs would jointly contribute to a higher degree of integration by about 20% to 30%. The Author 2013. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.